Contemporary developments in Waqf beneficiaries—a case study of the Awqaf of the United Arab Emirates - Arab, Sulaiman Haroon Yaqoob; Zakariyah, Habeebullah; Abdullatif, Abdullatif Mohammad (Springer Science and Business Media Deutschland GmbH, 2022)
This study aims to investigate the effectiveness of the Islamic waqf system in the contemporary Islamic societies and the significance of applying institutionalized systems for efficient administration and governance of waqf institutions. The study has been classified into theoretical and practical aspects. The theoretical aspect treats the concept of waqf, its classifications, the institutional development of the beneficiaries of contemporary waqf, and the legal and Shariah frameworks governing them. It highlights the major emerging and new waqf beneficiaries in the fields of education, health and relief. On the other hand, the practical aspect conducts a field study of waqf institutions. The study adopted both the inductive method and the descriptive approach employing the face-to-face interview method for collecting data as well as telephone interviews with interviewees. A number of conclusions emerged from the research, including a keen interest in waqf work and management practises, as well as an emphasis on the supervisory function. In addition, the concept of legislative stalemate was proposed. The study also discovered that current legislation and the renewal of jurisprudence provided waqf banks, as well as the general public, the freedom to develop successful new and creative banks to support their work